Evaluation of the anti-inflammatory, antinociceptive, and antipyretic potential of ethanolic extract of Aristida depressa Retz through in vitro, in vivo, and in silico models - Sherif, Asmaa E.; Alam, Rabia; Asif, Muhammad; Khan, Kashif-ur-Rehman; Ur Rehman, Muhammad Sajid (Frontiers in Pharmacology, 2024)
Uncontrolled inflammation is crucial to the development of many diseases. Natural sourcesbased anti-inflammatory molecules are actively studied and Aristida depressa Retz (Ar.dp) is traditionally used as a paste to heal inflammation. The present study was designed to evaluate the anti-inflammatory, analgesic and antipyretic potential of ethanol extract of A. depressa using a battery of in vivo and in vitro models. Ethanolic extract of Aristida depressa was prepared through maceration and chemically characterized through High-performance liquid chromatography (HPLC) technique that revealed the presence of quercetin, vanillic acid, chlorogenic acid, p-coumaric acid, m-coumaric acid, ferulic acid, cinnamic acid and sinapic acid.Antioxidants capacity was screened by DPPH in vitro assay and indicated moderate scavenging capacity of Ar.dp. A protein denaturation assay was performed to evaluate in vitro antiinflammatory potential of Ar.dp which showed significant inhibition (44.44 %) as compared to the standard drug (diclofenac sodium) with 89.19 % inhibition at 1 mg/ml. The in vivo safety profile of Ar.dp was evaluated following OECD-425 acute toxicity guidelines and was found to be safe up to 5 g/kg. In vivo anti-inflammatory potential of Ar.dp at three different doses (125, 250 and 500 mg/kg) was evaluated in acute (carrageenan 84.60 %) and, histamine-induced paw edema 84 %), sub-chronic (cotton pellet-induced granuloma 57.54 % and chronic (Complete Freund's adjuvant-induced arthritis 82.2 %) models. Our results revealed that Ar.dp showed significant (p < 0.05) anti-inflammatory effects as compared to diclofenac sodium in both acute and chronic models respectively. Histopathology studies displayed reduced infiltration of paw tissues with inflammatory cells in Ar.dp treated animals. Similarly, Ar.dp showed significant (p < 0.05) analgesic (yeast induced-pyrexia model 23.53%) and antipyretic (Acetic-acid-induced writhing model 51%) effects in a time-dependent manner. In silico studies describe the interaction of COX-1 and COX-2 with the ligands (chlorogenic acid, cinnamic acid, ferulic acid, m-coumaric acid, p-coumaric acid, quercetin, sinapic acid, vanillic acid) confirmed the inhibition of enzymes responsible for inflammation and fever. Based on the findings of the present study, it can be concluded that Ar.dp has anti-inflammatory, analgesic and antipyretic properties which are proposed to be linked with its pharmacologically active phenolic bioactive molecules.